2021
DOI: 10.1007/s40266-021-00838-6
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Recommendations for the Management of Older Adult Patients with Sjögren’s Syndrome

Abstract: Primary Sjögren's syndrome (SjS) is a systemic autoimmune disease most commonly diagnosed in middle-aged women. Although the disease can occur at all ages, it is diagnosed between 30 and 60 years of age in two-thirds of patients. In more than 20% of cases, the people are older than 65 years. In this review, we focus on the therapeutic management of primary SjS in older patients, following the recently published 2020 European League Against Rheumatism (EULAR) recommendations for the management of the disease wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…Clinical (15): studies in non-autoimmune populations have shown that the frequency of oral dryness is much higher in older people (16)(17)(18)(19)(20). This has been linked to progressive glandular ageing, and especially with the greater use of drugs in older people which has been closely associated with reduced salivary flow rates (19), especially in patients receiving ≥2 hyposalivatory drugs ( 21) and those with coexisting diabetes mellitus (22).…”
Section: S-170mentioning
confidence: 99%
“…Clinical (15): studies in non-autoimmune populations have shown that the frequency of oral dryness is much higher in older people (16)(17)(18)(19)(20). This has been linked to progressive glandular ageing, and especially with the greater use of drugs in older people which has been closely associated with reduced salivary flow rates (19), especially in patients receiving ≥2 hyposalivatory drugs ( 21) and those with coexisting diabetes mellitus (22).…”
Section: S-170mentioning
confidence: 99%
“…In more than 20% of cases, SS is diagnosed in people aged ≥65 years (11). When the disease is diagnosed at older ages, the frequency of dryness symptoms and abnormal diagnostic tests (parotid sialography, ocular tests, minor salivary gland biopsy) is similar to that reported in middle-aged people (12).…”
Section: Myth People Diagnosed At Older Ages Has a Milder Systemic Ex...mentioning
confidence: 55%
“…Cyclosporine is a traditional immunosuppressant, initially used in organ transplantation, that is now widely used in treating various autoimmune diseases, such as RA and pSS [ 51 ]. The 2020 European League Against Rheumatism recommendations for the management of pSS by topical and systemic therapy stated that cyclosporine showed acceptable safety as a drug that could be used topically [ 52 ]. Zidovudine and stavudine, thymidine analogues, are antiretroviral drugs that inhibit retroviral replication by disrupting viral reverse transcriptase and extending viral DNA strands [ 53 ].…”
Section: Discussionmentioning
confidence: 99%